Rancang Bangun Turbin Crossflow Pada Spiral Vortex Turbine House Sebagai Pembangkit Listrik Tenaga Pikohidro - Sigit Setya Wiwaha; Ferdian Ronilaya; Farhan Dhiya Ulhaq; M. Naufal Fariz Muhfid; Ricky Setyawan; Sri Wahyuni Dali (Elposys: Jurnal Sistem Kelistrikan, 2021)
The Javan Langur Center is a Javan langur rehabilitation center located in the middle of the Coban Talun forest. In the area there is a river that can be used as a Pico Hydro Power Plant with a crossflow turbine as its main component. The selection of a crossflow turbine aims to analyze the latest design of a crossflow turbine, to determine the effect of the number of blades on the turbine rotation speed in the PLTPH system and to regulate discharge to obtain maximum output. The research began with making 2D designs and then continued in 3D and applied in real form. Data collection is carried out by creating a workflow for the entire process with an analysis method using a comparison of test data and field measurements. After data collection and analysis, the turbine at 100% intake opening produced a turbine speed of 52 rpm without pulleys and produced an output of 18 volts with a current of 0.31 A when connected to a battery.